HIT training - Mechanisms of adaptation - Gibala, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Interval exercise refers to the basic pattern of alternating periods of more intense effort with period of less intense effort, or complete rest, within a single training session. Owing to the wide variety of terms used to describe this basic type of exercise, a classification scheme was recently proposed to delineate "high intensity interval training" (HIIT) from "sprint interval training" (SIT) (1). HIIT generally refers to submaximal exercise protocols in which the workload elicits a relative intensity corresponding to 80% of peak heart rate. SIT describes protocols in which the intensity corresponds to 100% of the workload that elicits maximal oxygen uptake (VO2max). Dating back several decades, numerous studies have examined physiological adaptations to HIIT and traditional moderate-intensity continuous training (MICT), matched for total work or energy expenditure. While these have yielded equivocal results, several recent systematic reviews and meta-analyses have concluded that HIIT elicits superior physiological adaptations in both average healthy individuals and people with lifestyle-induced cardiometabolic disease (1-3). Research over the last decade in particular has shed new light on the potency of lowvolume interval training, which involves a relatively small total amount of exercise, to elicit physiological adaptations that are comparable to MICT in a time-efficient manner (4). Studies that have directly compared MICT to low-volume HIIT or SIT protocols have reported similar improvements in markers of aerobic energy metabolism, as well as clinical indices of health status, despite large differences in total exercise and training time commitment. Recent evidence supports the general contention that exercise intensity is more important than duration for exercise training-induced increases in cardiorespiratory fitness (5). In contrast, the specific roles of intensity, duration and volume on aspects of exercise-induced skeletal muscle remodelling, in particular mitochondrial biogenesis, are equivocal (6). Recent work suggests the potential for SIT to promote greater and faster mitochondrial adaptations in human skeletal muscle than does HIIT or MICT despite a much lower training volume (7). It was also reported in humans that muscle fibre-type specific responses to SIT were strikingly similar to MICT despite lower training volume (8).